Cowpea (Vigna unguiculata L.) production, genetic resources and strategic breeding priorities for sustainable food security: a review - Kim, Dong-Kwan; Ochar, Kingsley; Iwar, Kanivalan; Ha, Bo-Keun; Kim, Seong-Hoon (Frontiers in Plant Science, 2025)
Cowpea is one of the most important staple crops, known for food security and agricultural sustainability. The crop has a multifaceted use, including food, feed, and soil fertility management. It is a staple food, especially in Africa and parts of Asia and the Americas, where it is valued for its rich nutritional content. Though cowpea is a climate resilient legume, the extent of its environmental adaptability and its utility value vary considerably across different production regions. Each region has unique conditions, including varying climates, soil types, and pest pressures. Given this versatile and diverse nature of cultivation environments, different varieties are needed to address all regional challenges. Breeding efforts often prioritize producing a range of varieties with different plant types, growth habits, and maturity periods in order to maximize yields and enhance environmental resilience, while also addressing region-specific needs. Meanwhile, genetic diversity among crop resources is essential for effective breeding, as targeted strategic breeding can significantly improve crop productivity, enhance market value, and better meet consumer preferences. With the aim to further strengthen research efforts in cowpea breeding for increased yield productivity for food security, this review examined recent global cowpea production, state of germplasm resources conservation and breeding priorities across different regions. Based on the current knowledge, further progress is required in addressing specific regional challenges, such as enhancing pest resistance, drought tolerance, and nutritional quality to ensure continued contribution of cowpea to global food security and agricultural sustainability.